1989
DOI: 10.1161/01.str.20.11.1516
|View full text |Cite
|
Sign up to set email alerts
|

Selective cortical neuronal damage after middle cerebral artery occlusion in rats.

Abstract: We studied histopathologic changes in cerebral cortex of 20 rats after middle cerebral artery occlusion by using the Fink-Heimer suppressive silver impregnation method and conventional stains. At 6 hours after occlusion, Fink-Heimer-stained sections revealed abundant coarsely granular, intensely argyrophilic neurons in the ischemic cortex. These distinctive argyrophilic neurons could be clearly differentiated from neurons that suffered postmortem changes; argyrophilic neurons were present in all layers of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Given previous imaging studies showing that axonal loss and demyelination associated with Wallerian degeneration (WD) can be detected in DTI as decreased FA and increased RD in white matter distant from the injury, 37,38 we hypothesize that our CC findings are due to WD caused by the left hemisphere lesion. 39 Our finding that increased lesion/ ROI overlap ratio in the left hemisphere predicted lower FA values in the whole CC ROI and CC-SMA ROI lends additional support to this hypothesis.…”
Section: Statistical Analyses All Statistical Analyses Were Done In supporting
confidence: 69%
“…Given previous imaging studies showing that axonal loss and demyelination associated with Wallerian degeneration (WD) can be detected in DTI as decreased FA and increased RD in white matter distant from the injury, 37,38 we hypothesize that our CC findings are due to WD caused by the left hemisphere lesion. 39 Our finding that increased lesion/ ROI overlap ratio in the left hemisphere predicted lower FA values in the whole CC ROI and CC-SMA ROI lends additional support to this hypothesis.…”
Section: Statistical Analyses All Statistical Analyses Were Done In supporting
confidence: 69%
“…In our previous studies, selective neuronal death in the peri-infarct cortex and subcortical area was obvious in FinkHeimer sections as early as 6 hours after MCAO and reached a maximum within 24 hours. 7 Kataoka et al 12 have reported decreased succinate dehydrogenase activity in ipsilateral thalamic neurons 5 days after MCAO. Although reports of human autopsy cases are few, neuronal degeneration or cell loss with GFAP reactions has been observed in the ipsilateral thalamus after cortical lesions including stroke, injury, and surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Whether increases in free radicals generated by xanthine oxidase contribute to tissue damage is unresolved. Most studies suggest that infarcts are complete by 4-6 hours, 17 yet uric acid increases persisted for 21 days and were maximal at 1 day. It is therefore possible that changes are merely secondary.…”
Section: Discussionmentioning
confidence: 99%